Particle-impact voltammetry: The reduction of hydrogen peroxide at silver nanoparticles impacting a carbon electrode - Stuart, E; Rees, N; Compton, R (2012)
The complete, two-electron reduction of hydrogen peroxide at silver nanoparticles during collisions of the nanoparticles with an inert carbon electrode is reported. The current passed during each impact (average duration 13 ms) is shown to be quantitatively approximated to that of the diffusion-limited current at an isolated NP-sphere of radius R, thereby enabling the sizing of the nanoparticles, and providing insight into future physical models of the contact environment. © 2012 Elsevier B.V. All rights reserved.